Fatigue analysis of woven intraply carbon/kevlar hybrid composite below ambient temperature - Majid, D.L.; Hashim, N.; Baitab, D.M.; Karunakaran, S. (Springer, 2024)
The low-cycle fatigue behavior of woven intraply carbon/Kevlar reinforced epoxy hybrid composites below ambient temperatures at 0, –5, and –10°C was investigated. Samples of woven intraply carbon/Kevlar reinforced hybrid composites were fabricated by means of vacuum infusion technique and tested for stress-controlled constant amplitude fatigue tests at stress ratio of 1 and 10 Hz within stress range of 60 to 90% of its tensile strength. The correlation between the elastic modulus and strength with the fatigue performance was established. Fatigue results showed linearized fatigue curves with larger scatter observed at –5 and –10°C. Using the maximum likelihood estimation (MLE), the life degradation rate at sub-zero temperature decreased from 5.2 to ~ 3% of its ultimate tensile strength. An inverse correlation between the degradation rate and the tensile strength was observed. In addition, surface temperatures were monitored during the fatigue cycles, and it was found that self-heating was significantly influenced by the fiber structures and its stiffening properties. At lower temperature, the heat generation also found to be influenced by the tensile modulus but did not affect the material fatigue properties.